Peningkatan Kapasitas Peternak di Desa Lolotuara Kecamatan Pulau Lakor - Heryanus Jesajas; Harmoko Harmoko; Asmirani Alam; Lestari Lestari; Edy Sony; Sigit Sugiarto; Ratna Kurniati; Dian Rubiana Suherman (Utan Kayu Publishing, 2023)
Increasing the capacity of farmers in an effort to increase livestock production is important, because with the increasing capacity of farmers, increasing livestock productivity will be easier to obtain. The implementation of Community Service was carried out in Lolotuara Village, Pulau Lakor Subdistrict in July 2022, participants in the extension for increasing the capacity of farmers were attended by villages, village officials and the livestock community. The results of the implementation of the extension in Lolotuara Village, Pulau Lakor Subdistrict, which was attended by the village head, village officials and the farmer community, gave quite positive results because the PKM team was well received and during the counseling process the participants asked many questions so that the farmers were able to understand a good livestock business improvement system.